INFORMATION SECURITY ISSUES (Conference Zone, 2022)
The advent of Internet technology has increased the ability to access information from a variety of sources quickly and easily to an unprecedented extent for everyone - from ordinary citizens to large organizations. Government agencies, science and education institutions, commercial enterprises and individuals have begun to create and store information in electronic form